2019
DOI: 10.1085/jgp.201912347
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants for agonist recognition and discrimination in P2X2 receptors

Abstract: P2X receptors (P2XRs) are ligand-gated cation channels involved in pain and inflammation. Gasparri et al. show that the backbone carbonyl atoms of amino acid residue Thr184 are involved in ligand discrimination, while those of Lys69 contribute mostly to ligand recognition by rat P2X2Rs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 52 publications
2
19
1
Order By: Relevance
“…Additionally, the approach does not rely on the ribosomal machinery and thus delivers a homogenous protein population by avoiding the potential for non-specific incorporation, which can affect protein manipulation using non-sense suppression approaches [32][33][34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the approach does not rely on the ribosomal machinery and thus delivers a homogenous protein population by avoiding the potential for non-specific incorporation, which can affect protein manipulation using non-sense suppression approaches [32][33][34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…While the location of the ATP-binding site in the extracellular domain is undisputed, the details of how conserved basic side chains coordinate the phosphate tail of ATP remain unclear 33 . However, ribosome-based non-sense suppression approaches, using e.g.…”
Section: Insertion Of Ncaas Into the P2x2 Receptor Extracellular Domainmentioning
confidence: 99%
“…They used molecular dynamics simulations to demonstrate that the loss of an intramolecular hydrogen bond between the 2′ hydroxyl and a γ-phosphate oxygen could destabilize the U-shaped conformation of ATP required for efficient agonist action. In terms of rat P2X2 receptors, Gasparri et al found that for 3′-dATP the EC 50 was increased by a factor of 3, but that 2′-dATP displayed very little agonist activity 33 . Similarly in our study, both 3′-and 2′-dATP displayed reduced activity compared to ATP, with 2′-dATP having the lowest activity, suggesting broad agreement between the agonist profiles of P2X1 and P2X2.…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge of the structure of the P2X binding pocket and its interactions with the primary ligand offers a unique opportunity to understand the mechanistic basis of ligand specificity of the receptor. The ligand specificity of P2X receptors has been explored in previous studies (reviewed in [30][31][32], and most recently in a systematic study of agonist recognition and specificity in rat P2X2 receptors 33 , where a series of ATP analogues with modifications to the base and ribose were examined. In our study we have further expanded the range of molecules tested on rat P2X2 by using a library of 80 adenosine nucleotides.…”
mentioning
confidence: 99%
“…The papers published by the winners attest to the quality of work in JGP . The awards were presented in San Diego by the Society of General Physiology (SGP) President, Crina Nimigean, to Stephan Pless (Cranefield Awardee) for his work on P2X receptors (Gasparri et al, 2019), Sarah Codding (Postdoc Award) for her study of hERG channels (Codding and Trudeau, 2019), and Aaron Bozzi (Student Award) for his work on metal transporters (Bozzi et al, 2019).…”
mentioning
confidence: 99%